Diagnosis and management of children with McArdle Syndrome (GSD V) in New South Wales - Louisa Adams; Arthavan Selvanathan; Kiera J. Batten; Nancy vanDoorn; Susan Thompson; Ashleigh Mitchell; Hugo Sampaio; Troy Dalkeith; Jacqui Russell; Carolyn J. Ellaway; Michelle Farrar; Carolyn Broderick; et al. (JIMD Reports, 2023)
Abstract Glycogen storage type V (GSD V—McArdle Syndrome) is a rare neuromuscular disorder characterised by severe pain early after the onset of physical activity. A recent series indicated a diagnostic delay of 29 years; hence reports of children affected by the disorder are uncommon (Lucia et al., 2021, Neuromuscul Disord, 31, 1296–1310). This paper presents eight patients with a median onset age of 5.5 years and diagnosis of 9.5 years. Six patients had episodes of rhabdomyolysis with creatine kinase elevations >50 000 IU/L. Most episodes occurred in relation to eccentric non‐predicted activities rather than regular exercise. One of the patients performed a non‐ischaemic forearm test. One patient was diagnosed subsequent to a skeletal muscle biopsy, and all had confirmatory molecular genetic diagnosis. Three were homozygous for the common PYGM:c.148C > T (p.Arg50*) variant. All but one patient had truncating variants. All patients were managed with structured exercise testing to help them identify ‘second‐wind’, and plan an exercise regimen. In addition all also had an exercise test with 25 g maltodextrin which had statistically significant effect on ameliorating ratings of perceived exertion. GSD V is under‐recognised in paediatric practice. Genetic testing can readily diagnose the condition. Careful identification of second‐wind symptomatology during exercise with the assistance of a multi‐disciplinary team, allows children to manage activities and tolerate exercise. Maltodextrin can be used for structured exercise, but excessive utilisation may lead to weight gain. Early intervention and education may improve outcomes into adult life.